TINJAUAN YURIDIS UNDANG-UNDANG PEMERINTAHAN DAERAH TENTANG KEGIATAN PERTAMBANGAN - Eko Nuriyatman; Trias Hernanda (Universitas Muara Bungo, 2020)
This scientific article contains writings about the juridical review of local government law regarding mining activities in Indonesia. In this article the researcher discusses two things, namely the authority of the regional government in mining and inconsistencies between local government laws and coal mineral laws. The research method used in writing this article is a normative research method, the legal concept used is that proposed by Soetondyo Wigyosoebroto who has five legal concepts, but in this article the author uses the second and fifth concept concepts presented by Soetondyo Wigyosoebroto. Based on the results of writing this article, it is found that after the issuance of Law Number 23 of 2014 the authority to grant mining activities permits lies with the provincial government and this is contrary to what is contained in Law Number 4 of 2009, so that in the application of the lex principle applies specialis derogate legi generalisi. The development of mining activities that occur in Indonesia has a very large impact on mining activities, with the authority for mining activities having the aim that management of mining activities is not centralized and can increase the economy and increase local revenue. Keyword: Regional Government, Mining, Licensing.